Elucidating the Potential Mechanisms Underlying Distraction Spinal Cord Injury-Associated Neuroinflammation and Apoptosis - Han, Bo; Liang, Weishi; Hai, Yong; Liu, Yuzeng; Chen, Yuxiang; Ding, Hongtao; Yang, Jincai; Yin, Peng (Frontiers in Cell and Developmental Biology, 2022)
The incidence of distraction spinal cord injury (DSCI), which results from spinal cord ischemia due to vascular compromise and spinal cord tract disturbances, remains high. Furthermore, because no ideal animal model that mimics DSCI in clinical settings is available thus far, the related molecular mechanisms underlying DSCI remain unclear. Thus, this study aimed to establish a porcine model of DSCI and investigate the neuroinflammation and apoptosis mechanisms in these pigs. Before surgery, all pigs were randomly divided into three groups: sham group, osteotomy surgery only; the incomplete distraction spinal cord injury (IDSCI) and complete distraction spinal cord injury (CDSCI) group, osteotomy plus DSCI surgery with a motor-evoked potential (MEP) amplitude decreased by approximately 75% and 100%, respectively. After surgery, modified Tarlov scoring and MRC muscle strength scoring were used to evaluate neurologic function in each group. We observed the distracted spinal cord using MRI, and then all pigs were sacrificed. Inflammatory cytokine levels in the spinal cord and cerebrospinal fluid (CSF) were also analyzed. We used immunofluorescence staining to assess the neuronal and microglial structure and function and astrocyte hyperplasia in the central DSCI lesions (T15). Western blotting was used to determine the expression of apoptosis-related proteins. Results showed that the modified Tarlov scoring and muscle strength decreased significantly in the two DSCI groups. T2-MRI showed a relative enhancement at the center of the DSCI lesions. H&E and Lxol fast blue staining revealed that spinal cord distraction destroyed the normal structure of spinal cord tissues and nerve fiber tracts, exacerbating inflammatory cell infiltration, hyperemia, and edema. The IL-1β, IL-6, and TNF-α levels increased in the spinal cord and CSF following DSCI. Immunofluorescence staining results indicated the GFAP, Iba-1 expression increased following DSCI, whereas the NeuN expression reduced. Moreover, DSCI promoted the protein expression of P53, Bcl-2-associated X protein (Bax), and Caspase-3 in the spinal cord tissues, whereas it reduced the Bcl 2 expression. This study successfully established a porcine DSCI model that closely mimics DSCI in clinical settings, and clarified the mechanisms underlying DSCI-associated neuroinflammation and apoptosis; thus, our findings highlight potential DSCI-treatment strategies for further establishing suitable drug therapies.